Biomimicking Vitamin b12 a Co Phthalocyanine Pyridine Axial Ligand Coordinated Catalyst for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Ltd, 2018)
CoN4 complexes like Co phthalocyanines (CoPc) have been extensively studied as electrocatalysts for the oxygen reduction reaction (ORR) but they only promote the 2-electron reduction of O2 to give peroxide. In contrast, vitamin B12 a Co macrocyclic naturally occurring molecule has attracted the attention of the scientific community because instead of catalysing the 2-electron reduction of O2 to H2O2 like the other Co macrocycles it promotes the 4-electron reduction to H2O. Vitamin B12 possesses an axial back ligand and this seems to be the reason for its higher activity and selectivity for the 4-electron reduction of O2. To test this hypothesis, we synthetized a CoPc axially coordinated to pyridine anchored to carbon nano-tubes (CoPc-Py-CNT). The Co centre is therefore coordinated to 5 N as in vitamin B12. The modified CoPc containing catalytic material was characterized by EPR and XPS spectroscopy. Ab initio calculations, Koutecky– Levich extrapolation and Tafel plots well describe the similarities between the 2 complexes and reveal insights into the mechanism of action of Co penta-coordinated complexes. According to our results the pyridine back ligand increases the Co-O2 binding energy and making it more similar to that of Vitamin B12, favouring the splitting of the O-O bond. The back ligand then plays a crucial role in modifying Co-O2 binding energy which is a well know reactivity descriptor. © 2018 Elsevier Ltd